Stereoselective Enzymatic Reduction of Ethyl Secodione: Preparation of a Key Intermediate for the Total Synthesis of Steroids. Issue 7 (18th February 2016) - Contente, Martina Letizia; Molinari, Francesco; Serra, Immacolata; Pinto, Andrea; Romano, Diego
Abstract: Ethyl secodione (1 ) has been enantioselectively reduced by using different biocatalysts for the preparation of ethyl secol (13 R, 17 S )‐2a . The recombinant ketoreductase KRED1‐Pglu converted the substrate with the highest reaction rate and stereoselectivity ( ee > 98 %), whereas whole cells of Pichia minuta CBS 1708 showed the highest productivity. Stereoselective reduction of1 provides the key chiral precursor for the synthesis of a number of hormonal contraceptives (i.e., desogestrel, norgestrel, gestodene). Abstract : Recombinant ketoreductase KRED1‐Pglu and whole cells of yeasts provide the key chiral precursor for the synthesis of a number of hormonal contraceptives (i.e., desogestrel, norgestrel, gestodene) with excellent stereoselectivity.